Culture and structure in the pharmaceutical industry - Haloub, Radi (Henry Stewart Talks, 2025)
Organisational culture, Layers of organisational culture, Values, Beliefs, Behaviours, Paradigm, Cultural web, Novartis case study, Strategic drift